Path integral's formulation of the molecular solvent effects - Marañón, Julio (1994)
With the formalism of the path-integral into molecular-orbital theory, we introduce the quaturn fluctuation into the molecular ground state. As a consequence, a non-linear formulation of the molecular orbitals is obtained. Then, we connect the non-linear term of the effective Hamiltonian with the solvent effects of the environment surrounding the molecular system, and explain this mechanism.